(3GdETGQI Edi ef fGd GdhRGQIs - (3CHh GdbGSe Ydj Hf efLH Hf SdjeGf, GHf GdUQaj GdeUQj,J (B550 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd GdKhGH Ydi bOQ GdELJgGO GdN hcGf Gdeedhc bO CNP ef Pdc HChaQ GdLRGA s
(3BNQgG (B:s
(3hLQO SDGd CejQ GdeDefjf hcJH GdSLd hGTJed Ydi JaUjdGJ s
(3Ydi QhGjI jGbhJ GdMeOi ChSfI (B542 (3Ydi QhGjI GHf ejSQ Vefg JQGLe hRQGA GdOhdI GdaGWejI ef YgO GdYRjR HGddg Edi GdBeQ HCMcGe Gddg hGHJOGg HJQLeI GdhRjQ CHj GdaQL jYbhH Hf cdS GdeJhai SfI (B390s
(3GdJhKjbGJ GdeQLYjI (B:s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B490 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B20 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs